"Cultural interaction between the ego of Arab west and the other Western ego " - Bakoush, Muftah Mohamed Mohamed Omar (Arab Journal for Sciences and Research Publishing, 2016)
Represented novel alienation real destination for cultural interaction between the ego Arab west and the other, especially in the aspects of the social and cultural life, I have sought writer Abdullah Laroui across the folds of this novel through his insistence on the inevitability of combining the core of the other gains and benefit from, according to Matanajh ego Arabic to regain its renaissance and comparable to Western culture and its development without alienation from the ego and thawing in the other trifles and hung scales civilizations that any writer calls for vision correction and select the path to be followed for the renaissance of the Arab community. The results of this paper that the relationship between the ego and the other long-term relationship with the Arab culture before it was prevalent in the world and got acculturation between them and the other was as a result of wars, as well as trade and two-way trips between East and West.